2016
DOI: 10.1111/imm.12670
|View full text |Cite
|
Sign up to set email alerts
|

An alternative mode ofCD43 signal transduction activates pro‐survival pathways of T lymphocytes

Abstract: SummaryCD43 is one of the most abundant co-stimulatory molecules on a T-cell surface; it transduces activation signals through its cytoplasmic domain, contributing to modulation of the outcome of T-cell responses. The aim of this study was to uncover new signalling pathways regulated by this sialomucin. Analysis of changes in protein abundance allowed us to identify pyruvate kinase isozyme M2 (PKM2), an enzyme of the glycolytic pathway, as an element potentially participating in the signalling cascade resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 79 publications
(89 reference statements)
1
10
0
Order By: Relevance
“…Recently, the inherent pro-inflammatory role of CD43; a co-stimulatory molecule of the T-cells were identified. It was shown that CD43 possesses the intrinsic ability to activate the NF-κB and cAMP response element-binding protein (CREB) pathways [ 30 ]. Furthermore, CD43 has been suggested to coordinate the expression of multiple cytokine genes and act as a chemotactic factor with a pro-adhesive role [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the inherent pro-inflammatory role of CD43; a co-stimulatory molecule of the T-cells were identified. It was shown that CD43 possesses the intrinsic ability to activate the NF-κB and cAMP response element-binding protein (CREB) pathways [ 30 ]. Furthermore, CD43 has been suggested to coordinate the expression of multiple cytokine genes and act as a chemotactic factor with a pro-adhesive role [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that CD43 possesses the intrinsic ability to activate the NF-κB and cAMP response element-binding protein (CREB) pathways [ 30 ]. Furthermore, CD43 has been suggested to coordinate the expression of multiple cytokine genes and act as a chemotactic factor with a pro-adhesive role [ 30 , 31 ]. This study for the first time investigated the possible modulatory effects of chitosan on the expression of hepatic and renal p53 and CD43, as well as hepato-renal functionality of hyperlipidemic rats.…”
Section: Discussionmentioning
confidence: 99%
“…PKM2 can also directly phosphorylate transcription factor and regulate its transactivation activity [ 20 ]. Nuclear PKM2 has been demonstrated to phosphorylate STAT3 at Tyr705 using a phosphate group from PEP, subsequently activating transcription of MEK5 [ 20 , 73 ] and HIF-1α [ 15 ]. The interaction of polypyrimidine tract-binding protein (PTBP1) and PKM2 facilitates phosphorylation of STAT3 Tyr705 and promotes oncogenesis in lymphoma [ 74 ].…”
Section: Protein Kinase Function Of Pkm2mentioning
confidence: 99%
“…Apart from these signaling molecules, some co-stimulatory molecules found on T-cell surface like CD43 also affect PKM2 expression and proliferation, activation and migration of T cells [86]. CD43 and TCR cosignaling stimulates the phosphorylation of Y105 of PKM2 and Y705 of Signal transducer and activator of transcription 3 (STAT3) transducer molecules resulting in the activation of MEPK5/ERk5 pathway which activates nuclear localization kappa B (NF-kB), Myc as well as Bcl-2-associated death promoter (BAD) phosphorylation promoting the survival [87]. Abnormal expression of this protein is also observed in some non-hematologic neoplasms such as lung, colon, and salivary gland cancers [86].…”
Section: T Cellsmentioning
confidence: 99%